Raw Material Inventory Analysis Using the Economic Order Quantity (EOQ) Method To Maximize Profits at UD. Panca Putra - Tesalonika F. Dagi; Jenny Morasa; Victorina Z. Tirayoh (Indonesian Journal of Business Analytics, 2023)
UD. Panca Putra carries out production by considering the costs that will come out in order to obtain maximum profit. One of the costs considered is the cost of raw material inventory. The purpose of this study is to determine the cost of raw material inventory UD. Panca Putra and to maximize company profits by using the Economic Order Quantity (EOQ) method and to find out how much the company's profit has increased by using the Economic Order Quantity (EOQ) method at UD. Panca Putra. The analytical method used is descriptive. The results of this study indicate that by using the Economic Order Quantity (EOQ) method, company profits have increased by 1.3%.